STUDI KUALITATIF PEMILIHAN KB VASEKTOMI DI KECAMATAN LEUWILIANG KABUPATEN BOGOR - Arsyati, Asri Masitha; Kresno, Sudarti (HEARTY, 2014)
This research describes the choice of vasectomy contraceptive and any factors under that choice. The vield area in two district village in Leuwiliang Rural Region which population of the member vasectomy contraceptive. This research strat form March to June 2011. This is Qualitative research with RAP (Rapid Assesment Procedure) design, using indepth interviews and document analysis. The number of informant samples are 42, consist of 10 keys informant, 16 vasectomy acceptors, 16 non vasectomy acceptors. The result shows factor influenced chosen of vasectomy contraceptive are good knowledge,motivation, child value, free of charge,and motivating from PLKB. However, wife support, difficult accessibility health services and myth factors that barrier of vasectomy contraceptive choice